ETHICS OF ENGLISH ON BUSINESS PRESENTATION - Al Hakim, Luqman (PROCEEDING INTERNASIONAL SEMINAR, 2015)
Business presentation is needed by persons to inform or persuade audience about certain topics. Through the presentation, information are clearly received by audience. So it needs many aspects to do, such as chronological order of presentation; clear language; good attitude and behavior; and polite ethics. Ethics is the standards one uses to determine right from wrong in terms of thought and behavior. It is one of major components of successful presentation. To do that, ones could adopt ethics from their own culture or culture where they are right now, i.e. in abroad. This paper here intends to show ethic of English business presentation and ethic of presentation to public in order to persuade audience to use the product/ program. It means that it is not to use on presentation of national or international seminar because the rule is not so detailed and complicated The business presentation based on the result of research and good communication is necessary to present objective information, therefore public will get clear and objective understanding. In fact, showing strengths on the own products and showing the weaknesses of others are prohibited to save the existence of brands.Keywords: ethics, business presentation